2022
DOI: 10.3390/plants11030371
|View full text |Cite
|
Sign up to set email alerts
|

Enriching Urea with Nitrogen Inhibitors Improves Growth, N Uptake and Seed Yield in Quinoa (Chenopodium quinoa Willd) Affecting Photochemical Efficiency and Nitrate Reductase Activity

Abstract: Quinoa is a climate resilience potential crop for food security due to high nutritive value. However, crop variable response to nitrogen (N) use efficiency may lead to affect grain quality and yield. This study compared the performance of contrasting quinoa genotypes (UAF Q-7, EMS-line and JQH1) to fertilizer urea enriched with urease and nitrification inhibitors (NIs; 1% (w/w) thiourea + boric acid + sodium thiosulphate), ordinary urea and with no N as control. Application of NIs-enriched urea improved plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Therefore, the combined application of urease inhibitors with nitrification inhibitors reduces multiple losses associated with volatilization and denitrification [ 206 ]. Urea with urease and nitrification inhibitors can be used simultaneously to improve the N uptake, seed yield and grain protein contents, for example in quinoa [ 207 ]. Meta-analysis by Yang et al [ 208 ].…”
Section: Innovations On the Fertilizer Marketmentioning
confidence: 99%
“…Therefore, the combined application of urease inhibitors with nitrification inhibitors reduces multiple losses associated with volatilization and denitrification [ 206 ]. Urea with urease and nitrification inhibitors can be used simultaneously to improve the N uptake, seed yield and grain protein contents, for example in quinoa [ 207 ]. Meta-analysis by Yang et al [ 208 ].…”
Section: Innovations On the Fertilizer Marketmentioning
confidence: 99%
“…Rehman et al [ 6 ] demonstrated, in Pakistan, that urea enriched with urease and nitrification inhibitors simultaneously can be used to improve the N uptake, seed yield, and grain protein contents in quinoa.…”
Section: Ecophysiological Traits and Adaptabilitymentioning
confidence: 99%
“…The window of plasticity for planting ranges from 15 October to 15 December and favorable time for its growth and yield potential is during November under irrigated conditions [17,34,36]. A delay in planting the crop usually prolongs growth, reduces grain filling, and delays crop maturity with a substantial reduction in seed yield [37] and response may be genotype specific [38][39][40][41].…”
Section: Production Practicesmentioning
confidence: 99%